THE EFFECT OF BOARD OF DIRECTOR, AUDIT COMMITTEE, INSTITUTIONAL OWNERSHIP TO FIRM VALUE, WITH FIRM SIZE, FINANCIAL LEVERAGE, AND INDUSTRIAL SECTOR AS CONTROL VARIABLES (STUDY ON LISTED COMPANIES IN INDONESIAN STOCK EXCHANGE PERIOD 2011-2015) - Samasta, Almira Santi; Muharam, Harjum; Haryanto, Antonius Mulyo (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2018)
This study aims to examine the effect of corporate governanceâ€™s mechanism to firm value which is proxied by Tobinâ€™s Q. This mechanism is divided into two, internal mechanism which is proxied by board of director and audit committee and external mechanism which is Â proxied by institutional ownership. This study is using control variables such as firm size, financial leverage and industrial sector.Sample used in this study are 40 companies which incorporated in several industrial sector in Indonesia which are listed in Indonesia Stock Exchange during 2011-2015. Hypothesis testing in this study is using multiple regression analysis.The result of this study shows that board of director has positive but insignificant effect to firm value in Indonesia, audit committee has positive and significant effect to firm value in Indonesia and institutional ownership has negative but insignificant effect to firm value in Indonesia. The control variables used in this study provide mixed results, where firm size has negative and insignificant effect to firm value, financial leverage has positive and significant effect to firm value and the whole industrial sector in Indonesia has no effect to firm value. From simultaneous test, this study shows that simultaneously independent variables significantly affect to firm value.